Comparison of seed traits of tropical (Indonesia) and temperate (New Zealand) orchid species to support orchid seed conservation : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy (PhD) in Horticultural and Agricultural Science at Massey University, Palmerston North, New Zealand - Diantina, Surya (Massey University, 2020)
Most orchid species are endangered, and a basic understanding of their seed biology is required to support conservation efforts. In particular, more knowledge of orchid seed characteristics would be useful for both 𝘪𝘯 𝘴𝘪𝘵𝘶 and 𝘦𝘹 𝘴𝘪𝘵𝘶 conservation. This comparative study used morphological and biochemical approaches to characterise and compare orchid seed qualitative and quantitative traits, to explore biochemical changes during natural seed ageing and to investigate different asymbiotic 𝘪𝘯 𝘷𝘪𝘵𝘳𝘰 seed germination media and cryopreservation techniques for 𝘦𝘹 𝘴𝘪𝘵𝘶 conservation. This study included six orchid species with different growth habits and distribution ranges (𝘋𝘦𝘯𝘥𝘳𝘰𝘣𝘪𝘶𝘮 𝘴𝘵𝘳𝘦𝘣𝘭𝘰𝘤𝘦𝘳𝘢𝘴, 𝘋. 𝘭𝘪𝘯𝘦𝘢𝘭𝘦, 𝘋. 𝘤𝘶𝘯𝘯𝘪𝘯𝘨𝘩𝘢𝘮𝘪𝘪 (𝘦𝘱𝘪𝘱𝘩𝘺𝘵𝘪𝘤), 𝘎𝘢𝘴𝘵𝘳𝘰𝘥𝘪𝘢 𝘤𝘶𝘯𝘯𝘯𝘪𝘯𝘨𝘩𝘢𝘮𝘪𝘪, 𝘗𝘵𝘦𝘳𝘰𝘴𝘵𝘺𝘭𝘪𝘴 𝘣𝘢𝘯𝘬𝘴𝘪𝘪 and 𝘛𝘩𝘦𝘭𝘺𝘮𝘪𝘵𝘳𝘢 𝘯𝘦𝘳𝘷𝘰𝘴𝘢 (terrestrial)) from temperate New Zealand and tropical Indonesia. Morphometric analyses revealed similarities in the qualitative traits of seeds and capsules at the genus level (𝘋𝘦𝘯𝘥𝘳𝘰𝘣𝘪𝘶𝘮). However, high variability in micro-morphological seed characteristics were observed in the orchid species in this study which were unrelated to their taxonomy, biogeographical origin, or growth habit, suggesting different ecological adaptations possibly reflecting different modes of dispersal. An investigation of the seed fatty acids showed that linoleic, oleic and palmitic acids (polyunsaturated, monounsaturated and saturated fatty acids, respectively) were the most abundant fatty acids in the seeds of all species and that rapid degradation of unsaturated acids occurred during ageing. Three epiphytic 𝘋𝘦𝘯𝘥𝘳𝘰𝘣𝘪𝘶𝘮 species had similar lipid composition but 𝘎𝘢𝘴𝘵𝘳𝘰𝘥𝘪𝘢 𝘤𝘶𝘯𝘯𝘯𝘪𝘯𝘨𝘩𝘢𝘮𝘪𝘪, 𝘗𝘵𝘦𝘳𝘰𝘴𝘵𝘺𝘭𝘪𝘴 𝘣𝘢𝘯𝘬𝘴𝘪𝘪 and 𝘛𝘩𝘦𝘭𝘺𝘮𝘪𝘵𝘳𝘢 𝘯𝘦𝘳𝘷𝘰𝘴𝘢 (terrestrial species) were characterised by the absence of erucic and palmitoleic acid. Changes in the proportion of oleic and linolenic acid were strongly correlated with seed viability loss. The ageing pattern was species-specific with 𝘋. 𝘴𝘵𝘳𝘦𝘣𝘭𝘰𝘤𝘦𝘳𝘢𝘴 being more vulnerable to lipid degradation. Epiphytic 𝘋𝘦𝘯𝘥𝘳𝘰𝘣𝘪𝘶𝘮 orchids had a less stringent media formulation requirement for seed growth than terrestrial orchids, and similarly, seeds of tropical species 𝘋. 𝘭𝘪𝘯𝘦𝘢𝘭𝘦 and 𝘋. 𝘴𝘵𝘳𝘦𝘣𝘭𝘰𝘤𝘦𝘳𝘢𝘴 germinated more easily than those of temperate species in this study. Cryopreservation with direct immersion of dry orchid seeds in liquid nitrogen is suggested as the most effective and efficient method for orchid seed conservation.
Keywords: Orchids; Seeds; Indonesia; New Zealand; Conservation; 300802 Horticultural crop growth and development